DIMENSI EPISTEMOLOGI PENDIDIKAN ISLAM - Yusuf, Mohammad Yasin (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2014)
Epistemology is the study of philosophy what investigates about the source, requirements, and the process of knowledge. In western epistemology studies, its known schools of thought, such as empiricism, rationalism and intuitisme. In Islamic thought studies is also several major streams in relation to the theory of knowledge (epistemology). There are at least three models of thought systems in Islam, its named Bayani, Burhani and Irfani. The third epistemology should be dialogue and go hand in hand. So with this assumption, try to be revealed various problems in Islamic education, particularly related to Islamic education epistemology, and then look for a new alternative epistemological reconstruction of thought which is certainly more realistic, innovative, transformative, accommodative, ekuilibratif and dynamic.